Anti-corruption campaign in China: An empirical investigation - Li Yang; Branko Milanović; Yaoqi Lin (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
Using official information published by Central Commission for Discipline Inspection (CCDI) of the CPC, we construct a database of officials who have been found guilty of corruption in China in the period 2012-21 with their personal characteristics and the amount of embezzled funds. We use it to investigate the correlates of corruption, estimate the effects of corruption on inequality, and find the expected increase in officials' income due to corruption and the gain in income distribution ranking. We find that the amount of corruption is positively associated with education, administrative (hierarchical) level of the official, and years of membership in the Communist Party. The sample of corrupt officials belongs to the upper income ranges of Chinese income distribution even without corruption. But corruption is a significant engine of upward mobility. While only one-half of the corrupt official would be in the top 5 percent of urban distribution without illegal incomes, practically all are in the top 5 percent when corrupt income is included.
Keywords: O12; D31; P37; 330; Corruption; Income Inequality; Income Distribution; China; Rent Seeking